Trafficking mechanism of bone marrow-derived mesenchymal stem cells toward hepatocellular carcinoma HepG2 cells by modulating Endoglin, CXCR4 and TGF-Î² - Mardomi, A; Sabzichi, M; Hussein Somi, M; Shanehbandi, D; Rahbarghazi, R; Taj Sanjarani, O; Samadi, N (Cellular and Molecular Biology, 2016)
Mesenchymal stem cells (MSCs) display differential migration ability toward different tumor-released factors. Migration of MSCs is highly important in induction of proliferation and invasiveness of hepatocellular carcinoma (HepG2) cells. In this study, the role of CXCR4/CXCL12 axis and TGF-Î²R signaling were evaluated in the migration of MSCs toward HepG2 cells. The MSCs were incubated with SDF-1Î± (CXCL12), antagonists of CXCR4, TGF-Î²R, and co-receptor of TGF-Î², (endoglin) for 48h. Then, the migration of these cells toward HepG2 cells was analyzed using in vitro migration assay. SDF-1Î± at a concentration of 100nM MSCs revealed the highest migration rate toward the conditioned medium (1.62 fold compared to the migration of un-treated MSCs; p<0.05). Applying combination of the antagonists against CXCR4, TGF- Î²R, and co-receptor of TGF-Î² decreased the migration rate significantly (4.51 fold; p<001). Western blot analysis confirmed that RhoA activity is a core modulator in migration pathway. This study demonstrated that CXCR4 and TGF-Î²R signaling are important for migration of MSCs toward HepG2 cells. Identifying the key mediators in the migration of MSCs toward hepatocellular carcinoma cells and then development of the therapeutic inhibitors against these factors can be considered as an essential strategy in suppression of tumor progression and metastasis.